Efektivitas Model Pembelajaran TGT Berbantu Pop Up Book dalam Meningkatkan Pemahaman Matematis Siswa MI Ma’arif Mayak - Silvia Margareta Putri; Hestu Wilujeng (Indonesian Mathematics Education Journal, 2024)
Based on the prerequisite tests that were carried out in class VI, MI Ma'arif Mayak students found that there were 17 students who got scores below the KKM and 8 students who got scores above the KKM. These results show that students' mathematical understanding is still low. The aim of this research is to find out: (1) Analyzing the application of the TGT type cooperative learning model assisted by pop up book media (2) Analyzing the application of the contextual learning model assisted by image media (3) Knowing the differences between the two learning models (4) Knowing the effectiveness of the two models learning. This research was designed using quantitative experimental methods with a quasi-experimental research design. Data collection was carried out by means of written tests and observation sheets. The data analysis technique in this research uses n-gain (%) and t test. Based on the results of the analysis, it can be seen that (1) The implementation of the TGT model assisted by pop up books can be carried out well. (2) The implementation of the contextual model assisted by image media can be carried out quite well. (3) There is a difference between the TGT type cooperative learning model assisted by pop up books and the contextual learning model assisted by image media in improving mathematical understanding for class V MI Ma'arif Mayak. (4) N-Gain (%) also shows that the experimental class is in the quite effective category while the control class is in the less effective category.